PENATALAKSANAAN FISIOTERAPI PADA KONDISI LOW BACK PAIN SPONDILOSIS LUMBAL DENGAN MODALITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN WILLIAM FLEKSI EXERCISE DI RSUD BENDAN KOTA PEKALONGAN - Martharina Friska Pasha; Nur Susanti (LPPM Universitas Pekalongan, 2015)
Low back pain is a syndrome characterized by major symptoms of pain or a feeling of discomfort in the lower back region and the surrounding bone. Spondyloarthropathy derived from the Greek word for spine. Lumbar spondylosis may imply changes in the spinal joints, characterized by increasing degeneration of the intervertebral discfollowed by changes in bone and soft tissue, or it can mean an overgrowth of bone (osteophytes), which are mainly located in the anterior aspect, lateral, and posterior sometimes from the edge of the superior and inferior vertebrae centralis (corpus).To provide an effective and efficient treatment, then performed a physiotherapy management. Implementation includes any action that checks physiotherapy pain with Sekala Five Story, spasme examination by palpation, examination by range of motion with the midline, and checks the value of muscle strength with Manual MuscleTesting (MMT).In this case to overcome the problems above can be used modality Transcutaneous Electrical Nerve Stimulation in the form of William Flexes And Exercise. After therapy six times, in getting results in a decrease in tenderness, and pain of motion, increase muscle strength in the trunk region, and increase range of motion in the trunk region. Evaluation on the sixth therapy for functional activity using oswestryability disability index showed an increase infunctional activity.Keywords : Low Back Pain Spondilosis Lumbal, Transcutaneous Electrical Nerve Stimulation and William Flexion Exercise.